العيد ودوره في تنمية العلاقات الاجتماعية في المجتمع الموصلي: دراسة سوسيوانثروبولوجية لعاداته وتقاليده - حامد، نجلاء عادل (جامعة الموصل - كلية التربية الأساسية, 2018)
يستعد الموصليون لاستقبال العيد قبل مقدمه بأيام عديدة، فتقوم النساء بتنظيف البيوت، وشراء الملابس وحاجات العيد، وعمل الكليجة، وشراء البهارات الخاصة بها. إلى جانب مستلزماتها الأخرى، التي تعد من المظاهر الثقافية الاجتماعية الموسمية العميقة الجذور عندهم، وتعمل منها كميات تكفي للعائلة وضيوفها إلى جانب قسم يوزع على الجيران والفقراء أيضا. أما الاحتفال بعيد الفطر وعيد الأضحى السعيدين فعادة ما تمارس في مدينة الموصل، زيارة الأقارب والأصدقاء عقب صلاة العيد وزيارة المقابر، ثم يقوم الأطفال بالتردد على الأقارب للاحتفال بالعيد وليأخذوا العيدية من أهليهم وأقاربهم، وهم بملابسهم الجديدة، ليذهبوا بعدها إلى المراجيح ومدينة الألعاب. كما ويجتمع أفراد العائلة مع أقاربهم لتناول طعام الغداء في أيام العيد المبارك في بيت الجد أو كما يسمى بيت العائلة في أول يوم العيد. يتبعها زيارة للأقارب وطبقا للعادات الاجتماعية في الموصل تتمثل بزيارة الأصغر سنا للأكبر سنا. وهناك تقليد لابد من وجوده عند الزيارات وهو ضرورة تناول الكليجة وشرب الشاي، لأنها تعبر عن آداب الضيافة الملزمة في أيام العيد. وعلى الرغم من سيادة نمط الحياة الحضرية على حياة المجتمع الموصلي الأصيل، الذي يجمع ما بين الأصالة والحداثة، فأننا سنتحدث عن عناصر ثقافية انجزها هذا المجتمع عبر تاريخية الطويل، ونتتبع إنجازاته اللا مادية المتمثلة في العادات والتقاليد الاجتماعية الخاصة بعيد الفطر وعيد الأضحى المباركين، وهذه المعطيات التراثية، سوف تعطينا فكرة عن الأساليب والطرائق التي نظم بمقتضاها مجتمع الموصل حياته الاجتماعية خلال أيام العيد المبارك في شتى جوانبها ومختلف نواحيها.
The Mosulic people are ready to celebrate a feast before it comes by many days. Women are cleaning their houses, buying clothes and feast’s needs . They are making pastry ( klaycha) and its special spicies, beside of its necessary needs which is considered as social cultural phenomena , which is also considered as something deer rooted . these people make a lot of pastery for their families and their guests . some of these pastry were distributed to neighbors and poor people. For fast feast and greater bairam in Mosuliccity, the visit of graves , the visit of relatives by children to celebrate a feast and take money from their families and their relatives , is considered as a phenomena of a feast ( Eed) . The children , with their new clothes , are going to swaying and lonapark. The members of the family gather together with their relatives to eal lunch in grandfathers house , during the days of a feast , especially in the first day of feasts days. After that, and according to special habits in mosulic society , the visit of relatives , which includes the gouger and older oyez. There is a necessary habit in a visit which is the necessity of eating pastry (klaycha) and drinking tea, because it expresses the good receiving , it is considered as a commit . Despite of the over coming of urban life over mosulic origin society , which combines the originality and modern a laity , we will take about cultural elements which is achieved by this society across its long history , and we trace its abstract achievements which stands for social habits and conventions especially in fast feast ( smaller Eed) and greater bairam . This tradition data , will give us an idea about methoods and styles which is considerable as the organization of mosulic society life during feat`s days in different sides .
Keywords: العلاقات الأسرية -- العلاقات الاجتماعية -- الترابط الاجتماعي -- المناسبات الدينية -- العادات والتقاليد